Determinants of Tax Efficiency in the Basic and Chemical Industry: The Moderating Role of Liquidity - Kurnia Heriansyah; Lazarus Sinaga; Cotoro Mukri (SAINTIS Publishing, 2025)
This study explores tax efficiency practices in Indonesia’s basic and chemical industry sectors during the economic uncertainty of the COVID-19 pandemic. It examines the influence of profitability, capital structure, capital intensity, and audit committee on tax efficiency, with liquidity as a moderating variable. Employing a quantitative causal associative approach and Structural Equation Modeling Partial Least Squares (SEM-PLS) using SmartPLS 3.3.2, the research analyzes 9 IDX-listed companies from 2019 to 2023. The results show that capital intensity and audit committee positively affect tax efficiency, while profitability and capital structure have no significant impact. Liquidity does not directly influence tax efficiency but strengthens the relationship between capital structure and capital intensity with tax efficiency. However, liquidity does not moderate the effects of profitability and audit committee. The findings indicate that in capital-intensive industries, tax efficiency is more influenced by asset utilization and governance mechanisms rather than profitability or leverage. The study emphasizes the importance of firm-specific characteristics in tax planning, especially during macroeconomic volatility. It contributes to the discourse on ethical and sustainable tax management by offering insights for policymakers and corporate financial managers on the role of liquidity and internal governance in shaping tax behavior